Synthesis of Alicyclic 2-Methylenethiazolo[2,3-b]quinazolinone Derivatives via Base-Promoted Cascade Reactions - El Haimer, Mohamed; Faragó, Tünde; Schelz, Zsuzsanna; Zupkó, István; Palkó, Márta (Synthesis, 2021)
The synthesis of alicyclic 2-methylenethiazolo[2,3-b]quinazolinones is performed via base-promoted cascade reactions, starting from either alicyclic β-amino propargylamides using carbon disulfide, or from alicyclic ethyl 2-isothiocyanatocarboxylates by addition of propargylamine. In both cases the cascade reaction proceeds by way of a favoured 5-exo-dig process during the second ring closure, as confirmed by full NMR spectroscopic assignments. Moreover, a high-yielding retro-Diels–Alder (RDA) reaction is performed on the norbornene derivatives leading to 2-methylene-2H-thiazolo[3,2-a]pyrimidin-5(3H)-ones. The obtained compounds exert modest antiproliferative activities against a panel of human gynaecological cancer cell lines.
Keywords: 2-methylenethiazolo[2,3-b]quinazolinones; propargylamine; fused quinazolinones; domino ring closure; 5-exo-dig